Design and Properties of Magnetically Controlled Sorbents - Butusova, O.A. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, the main parameters and advantages of magnetically controlled sorbents are considered. A large surface of nanodispersed magnetically controlled sorbents adsorbs large amounts of toxins, therefore, the consumption of magnetically controlled sorbents in each operation is insignificant. The ability to quickly replace the spent magnetically controlled sorbents in the detoxification apparatus with a new portion of magnetically controlled sorbents increases the reliability, simplicity and ease of use of the method under consideration. The small thickness of the sorbent layer and the availability of the sorbent surface provide almost instantaneous establishment of equilibrium concentrations, which significantly reduces the required processing time for the biofluid and increases the productivity of the purification process.